APPLICATION PRACTICE QUESTION â€œXâ€ USING VISUAL BASIC 6.0 - Agustinus Supriyanto; Irfan, SKom, MM Irfan, SKom, MM (Jurnal Sistem Informasi, 2002)
Many things hinder academic achievement is less frequent between to practice.Exercises to practice here in the form of either the old or the matter is still newthough. Exercises can be done in a very simple system, collect the questions that weneed then is read or discussed one by one. But it was not easy as it requires a highpersistence, because with so many of these questions require a lot of time too.Sometimes the way is not practical, throw-a waste of time.In the course of this exercise, the authors try to present a way that is expected tofacilitate the learning process. With this program there are questions which arecollected into one and then with the questions we can practice. Very simple form ofpresentation, in the form "Problem" by the time we practiced about 60 menis to do asmany as 100 fruits. If time runs out can no longer do. Then the result can be seen inthe forms "View Results". To keep the matter in accordance with the needs to showalso a matter of form to add and delete questions. This is necessary because thematter is there are sometimes no longer needed. To maintain the security of data inthe form "Add Question" and "Delete Question" is also included into the code. In theform "Add Question" can be done about their choices and the addition the answercorrect. Form "Delete Question" option presents a problem in the form of list makingit easier and deletion this matter can not be all about removed, as in the form"Problem" takes a minimum of 100 pieces of matter. In the form "See Results" can beviewed names, no. examinations and ratings of the value of the shape of large tosmall.